The Feast: a Cultural Tradition Made Popular - MSc. Dunia Eduvijes Jara-Solenzar (Santiago, 2015)
The party  is a social phenomenon  since the emergence  of human  society  mean  for people  a moment of relaxation. Therefore, interest in  the study  lies  in the discussion  of popular culture  from different perspectives  from the field of anthropology, sociology  and history.  In this context  theoretical approaches  are  defined  by  the relationship with the  ritual  and sacred,  in  the  space-time, space-ritual  relationship,  and the transgressive aspects.  In this way,  the holiday  experience-logical  historical  evolution  of the subject matter  discussed. Therefore, the  analysis  reveals  festive  phenomenon  in  practice the social meaning  it occupies in the  interpretive system  of subjects from their community action. Keywords: holiday, traditional popular culture, cultural identity.